THE EFFECT OF WORK FAMILY CONFLICT AND WORK LIFE BALANCE ON FEMALE TEACHER PERFORMANCE IN SMK NEGERI 1 BANDAR LAMPUNG - Betty Magdalena; Viola De Yusa; Dimas Ramadan (SEAN Institute, 2022)
The purpose of this study was to find out the effect of Work Family Conflict on the performance of female teachers in SMK Negeri 1 Bandar Lampung, the effect of work life balance on the performance of female teachers in SMK Negeri 1 Bandar Lampung, and the effect of work family conflict and work life balance on the performance of female teachers in SMK Negeri 1 Bandar Lampung. The type of study quantitative and associative method. The sources of data in this study was primary data in the form of questionnaires. The data collection method in this research was field research by distributing questionnaires. The population in this study was 105 teachers with the total sample of 35 female teachers. The sampling technique in this study used the non-probability sampling, namely the purposive sampling technique. The instrument requirements test in this study used validity test and reliability test. The data analysis requirements test in this study used the normality test, linearity test and multi-collinearity test. The data analysis method used the multiple linear regression and the hypothesis testing used t-test and F-test. The result of this study found that Work Family Conflict affected the performance of female teachers at SMK Negeri 1 Bandar Lampung, Work Life Balance affected the performance of female teachers at SMK Negeri 1 Bandar Lampung, Work Family Conflict and Work Life Balance affected the performance of female teachers at SMK Negeri 1 Bandar Lampung. The data analysis method used the multiple linear regression and the hypothesis testing used t-test and F-test. The result of this study found that Work Family Conflict affected the performance of female teachers at SMK Negeri 1 Bandar Lampung, Work Life Balance affected the performance of female teachers at SMK Negeri 1 Bandar Lampung, Work Family Conflict and Work Life Balance affected the performance of female teachers at SMK Negeri 1 Bandar Lampung. The data analysis method used the multiple linear regression and the hypothesis testing used t-test and F-test. The result of this study found that Work Family Conflict affected the performance of female teachers at SMK Negeri 1 Bandar Lampung, Work Life Balance affected the performance of female teachers at SMK Negeri 1 Bandar Lampung, Work Family Conflict and Work Life Balance affected the performance of female teachers at SMK Negeri 1 Bandar Lampung.